The effect of the microstructure on the antiferromagnetic to ferromagnetic transition in FeRh alloys. (1st June 2017) - Chirkova, A.; Bittner, F.; Nenkov, K.; Baranov, N.V.; Schultz, L.; Nielsch, K.; Woodcock, T.G.
Abstract: A detailed study of Fe48 Rh52 samples heat treated at different temperatures (1123 K, 1273 K and 1423 K) has been performed using scanning and transmission electron microscopy, energy dispersive x-ray spectroscopy, x-ray diffraction and magnetic measurements. The microstructure of all samples consisted of α′ (B2) and γ (A1) phases. Although the chemical composition, chemical ordering and the lattice parameter of the magnetic α′ phase in all three samples did not vary with heat treatment temperature, the temperature of the metamagnetic transition between the antiferromagnetic (AFM) and ferromagnetic (FM) states varied by 50 K. No gradients in chemical composition on a length scale larger than approximately 10 nm exist at the α′/γ phase boundaries. Due to the 1% volume expansion of the α′ phase, which occurs during the AFM-FM transition, stress fields around the α′/γ phase boundaries are expected. The composition, lattice parameter, size, shape and distribution of the γ phase was shown to change with heat treatment temperature. Finite element models indicated that these microstructural parameters influence the magnitude and extent of the stress fields at the phase boundaries. The variation in the transition temperature is therefore ascribed to the differences in the stress fields. Graphical abstract: Image 1